Egy késő-Ming kétnyelvű glosszárium helyreállításának tanulságai - Apatóczky, Ákos Bertalan (Távol-keleti Tanulmányok, 2017)
The author introduces his research into the linguistic and philological history of the bilingual chapters (Yibu 譯部) of the late Ming military treatise, the Lulongsai lüe 盧龍塞略 (LLSL). He argues that the linguistic data of the work hitherto treated as a representative of an Early Mandarin and a Middle Mongol linguistic state cannot be viewed as such, since all material of the compilation was in fact copied from other earlier works. Proofs for all the unveiled sources are introduced along with the shockingly few occurrences of original entries of the LLSL Yibu. A key consequence of the research is that this linguistic data due to its heterogeneity cannot be used to demonstrate 17th century linguistic status.